SIRT1 regulates differentiation of mesenchymal stem cells by deacetylating β‐catenin. Issue 3 (30th January 2013) - Simic, Petra; Zainabadi, Kayvan; Bell, Eric; Sykes, David B.; Saez, Borja; Lotinun, Sutada; Baron, Roland; Scadden, David; Schipani, Ernestina; Guarente, Leonard
Abstract Mesenchymal stem cells (MSCs) are multi‐potent cells that can differentiate into osteoblasts, adipocytes, chondrocytes and myocytes. This potential declines with aging. We investigated whether the sirtuin SIRT1 had a function in MSCs by creating MSC specific SIRT1 knock‐out (MSCKO) mice. Aged MSCKO mice (2.2 years old) showed defects in tissues derived from MSCs; i.e. a reduction in subcutaneous fat, cortical bone thickness and trabecular volume. Young mice showed related but less pronounced effects. MSCs isolated from MSCKO mice showed reduced differentiation towards osteoblasts and chondrocytes in vitro, but no difference in proliferation or apoptosis. Expression of β‐catenin targets important for differentiation was reduced in MSCKO cells. Moreover, while β‐catenin itself (T41A mutant resistant to cytosolic turnover) accumulated in the nuclei of wild‐type MSCs, it was unable to do so in MSCKO cells. However, mutating K49R or K345R in β‐catenin to mimic deacetylation restored nuclear localization and differentiation potential in MSCKO cells. We conclude that SIRT1 deacetylates β‐catenin to promote its accumulation in the nucleus leading to transcription of genes for MSC differentiation.